Seasonal Monitoring of Volatile Organic Compounds and Trihalomethanes in Sungai Sarawak Kiri: A Study of Batu Kitang Water Treatment Plant - Lim, Siong Hee; Sam Froze, Jiee; Romano, Ngui; Kueh, Tze Siew (RSIS International, 2026)
This study evaluates the occurrence of volatile organic compounds (VOCs) and trihalomethanes (THMs) in raw and treated water from the Batu Kitang Water Treatment Plant, Sarawak, Malaysia. Sampling occurred seasonally over one year at the inlet and outlet stages of the treatment process. All samples were analyzed for BTEX compounds and regulated THMs using gas chromatography–mass spectrometry (GC-MS). Results consistently showed concentrations below the method detection limits, indicating the effectiveness of the conventional treatment system and minimal contamination from the urban catchment area. This longitudinal study highlights the robustness of tropical water treatment systems and contributes to the regional dataset on disinfection by-products in Southeast Asia. Recommendations are provided for continued monitoring and potential inclusion of emerging contaminants.